EXECUTIVE INFORMATION SYSTEM (EIS) UNTUK MONITOR TINGKAT KEJAHATAN DI LAUT INDONESIA - Heru Lumaksono; Markus Tukan; Buhari Buhari (Universitas Islam Madura, 2020)
The marine security agency or called Bakamla is an institution that has the duty to carry out safeguards, supervision, prevention and enforcement of violations of law in the Indonesian sea area. Bakamla has a strategic role in safeguarding Indonesia's sea sovereignty, therefore Bakamla requires an Executive Information System (EIS) to be able to access data and information, so that problems can be identified, exploration of solutions, and become the basis for strategic marine security planning processes. The purpose of this study is to build an EIS prototype to monitor crime rates in the sea of Indonesia, this application was built with the waterfall method which is a sequential process design which in the process looks like a waterfall flow from the concept design process, project identification, analysis, design, coding, testing, implementation and maintenance. The EIS that was built has been able to integrate internal and external data with report output that is useful for managers and executives to find the best solution to crime in the Indonesian sea. The results of the EIS report on violations throughout 2016 in the Indonesian sea are: the western region is 165 crimes, the middle region is 118 crimes and the eastern region is 64 crimes. The crimes that occurred in the Indonesian sea were recorded by EIS based on the type of crime, where they occurred, the perpetrators and the state's losses due to the crime. With this EIS Bakamla easily made strategic decisions to minimize crime in the Indonesian sea.